Prospects for mine geological work in the intelligence age: Architecture of the intelligent geological guarantee technology system for mine exploitation - Yucheng XIA; Xueyang SUN; Lintian MIAO; Chen GUO; Rongjun DU (Meitian dizhi yu kantan)
Background and Significance In response to the serious challenges posed by the goals of peak carbon dioxide emissions and carbon neutrality, the intelligentization of coal mines is an inevitable course and a significant sign of the high-quality, sustainable development of the coal industry in the New era. Mine geological work, providing geological foundation and guarantee for underground coal mining, plays an increasingly significant role in the transformation and upgrading of the coal industry for high-quality development. Constructing an intelligent geological guarantee technology system for coal mining by combining mine geology with artificial intelligence (AI) can provide a comprehensive, whole-process geological guarantee for safe, efficient, green, and intelligent coal mining. Therefore, building such a technology system represents the development target and inevitable trend for mine geological work to match the goal of the intelligent construction of coal mines in the new era. The technology system will surely become the novel productivity that boosts the quality and efficiency of mine geological work. Methods and Results By exploring the scientific connotation of the technology system, this study preliminarily established the architecture of the technology system. Then, this study systematically sorted the five subsystems of the technology system (i.e., the intelligent management subsystem for fundamental geological survey information, the intelligent prediction and early warning subsystem for geologic hazards in mines, the intelligent monitoring, prediction, and early warning subsystem for ecosystems in mining areas, the intelligent identification subsystem for favorable mining blocks, and the transparent mining face subsystem), as well as their core modules. ConclusionsNotably, with the constant advancements in technologies for geological explorations and detections, the effectiveness of the technology system depends on the accuracy and reliability of original data, ultimately relying on the number and professional quality of personnel engaged in geological surveys. Therefore, it is necessary to further strengthen the introduction and cultivation of professionals in the field of mining geology.